1992
DOI: 10.1073/pnas.89.6.2384
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin binding in the rat heart atrium.

Abstract: Relaxin is a member of the insulin family of polypeptides that is best known as a reproductive hormone. In an effort to elucidate the mechanism of action of relaxin we previously localized the specific binding sites of a 32P-labeled relaxin in the rat uterus and brain. These studies suggested that, in addition to its classical role in pregnancy, relaxin might have other physiological functions. In the present paper we describe the specific and high-afminity binding of relaxin to the cardiac atrium of both male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 36 publications
1
60
0
1
Order By: Relevance
“…Oestrogen is considered to be one of the candidate factors regulating RLN receptor, but the effect is different between tissues and/or genders. Administration of oestradiol-17b into female rats increases the RLN-binding sites in the uterus but has no effect in atria and cerebral cortex, whereas the identical treatment in male rats reduces the RLN-binding sites in these tissues (Osheroff et al 1992, Tan et al 1999. More recent studies in neonatal porcine uterus and cervix have shown an increase in PXFP1 expression by oestradiol-17b administration (Yan et al 2008a).…”
Section: Discussionmentioning
confidence: 95%
“…Oestrogen is considered to be one of the candidate factors regulating RLN receptor, but the effect is different between tissues and/or genders. Administration of oestradiol-17b into female rats increases the RLN-binding sites in the uterus but has no effect in atria and cerebral cortex, whereas the identical treatment in male rats reduces the RLN-binding sites in these tissues (Osheroff et al 1992, Tan et al 1999. More recent studies in neonatal porcine uterus and cervix have shown an increase in PXFP1 expression by oestradiol-17b administration (Yan et al 2008a).…”
Section: Discussionmentioning
confidence: 95%
“…Relaxin has been reported to enhance cAMP formation in human endometrial (29) and anterior pituitary cells (30), to inhibit Ca 2 ϩ influx in myometrial cells (31) and mast cells (32), and to induce protein kinase C translocation from cytosol to membranes in endometrial cells (33). Additionally, binding of relaxin to certain cell types is estrogen-dependent while binding to others is not (34), and certain phenotypic alterations are dependent on the presence of both relaxin and estrogen while others are not (17). Cells derived from reproductive tissues, such as the cervix and uterus, tend to depend on estrogen pre-exposure in vivo, while binding to (34) and phenotypic effects on cells from nonreproductive tissues, such as skin or lungs (Unemori, unpublished observations), tend to be estrogen-independent.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, binding of relaxin to certain cell types is estrogen-dependent while binding to others is not (34), and certain phenotypic alterations are dependent on the presence of both relaxin and estrogen while others are not (17). Cells derived from reproductive tissues, such as the cervix and uterus, tend to depend on estrogen pre-exposure in vivo, while binding to (34) and phenotypic effects on cells from nonreproductive tissues, such as skin or lungs (Unemori, unpublished observations), tend to be estrogen-independent. In summary, we have found that relaxin can induce an extracellular matrix-degrading phenotype in human lung fibroblasts in vitro and can inhibit lung fibrosis in a murine bleomycin model.…”
Section: Discussionmentioning
confidence: 99%
“…This is apparently due to a much lower density of relaxin receptors in the atria of humans than that in rodents. 41 Thus, relaxin's tachycardiac effects should not be a clinical concern.…”
Section: Discussionmentioning
confidence: 99%